الشكر في القرآن الكريم: دراسة دعوية - آل عبدالهادي، حسن بن عائض بن عبدالهادي بن عائض (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2019)
إنَّ القرآن الكريم هو: دستور الحياة، وليس مجرد كتاب يُتلى للتبرّك، ومن يمعن الفكر في الآيات التي تتحدث عن الشكر يُدرك أن هذه العبادة العظيمة وهذا الخُلُقَ الكريم قد أوجبه الله تعالى ليكون منهج حياة العابدين. ومن العبادات العظيمة التي أنعم الله بها على الناس شكره تعالى على ما أولاهم من النعم الظاهرة والباطنة، والشكر حق من حقوق الله على عباده. وقد أمرنا عز وجل به في مواضع كثيرة من كتابه الكريم فأهمية الموضوع وأسباب اختياره: الشكر له مقامات عظيمة في الدين، وهو من مراتب إيّاكَ نعبدُ وإيّاكَ نستعين؛ بل من أعلى منازلها، وقد ورد ذكره في القرآن الكريم في خمسة وسبعين موضعاً بألفاظ عدة، ومما يدل على أهمية الشكر: أن الله أمر به، ونهى عن ضده، وأثنى على أهله، ووصف به خواص خلقه، وجعله غاية خلقه وأمره، و وعد أهله بأحسن جزائه، وجعله سبباً للمزيد من فضله، وحارساً وحافظاً لنعمته، وأخبر أن أهله هم المنتفعون بآياته. وقد قرن الله ذكره بشكره وكلاهما المراد بالخلق والأمر، والصبر خادم لهما ووسيلة إليهما وعوناً عليهما، الشكر أمان من عذاب الله، فالشاكر يحصل له الأمان من عذاب الله تعالى بخلاف المنافق المعر لعذاب الله عز وجل، قرن الله الشكر بالإيمان، وأنه لا غرض له في عذاب الخلق إذا قالوا آمنا. إن الشكر من أهم الأسباب لحصول رضا الرب تبارك وتعالى ولأهمية الشكر وعظم منزلته في الدين استعنت المولى -عز وجل ذكره- في البحث في هذا الموضوع وعنوانه (الشكر في القرآن الكريم) مع تفرعه وتعلق الآيات بعضها ببعض في ألفاظ الشكر والمعاني الدالة عليه وقسمت البحث إلى ثلاثة فصول وأوردت آيات الشكر حسب ما تقتضيه المباحث والمسائل المتعلقة بها دراسة تفسيرية موضوعية وبنيته على الخطة التالية: وقد استخدمت المنهج الوصفي التحليلي والذي يعرف بأنه ((الجمع المتأني والدقيق للسجلات والوثائق المتوافرة ذات العلاقة بموضوع البحث، ومن ثم التحليل الشامل لمحتويات البحث بهدف استنتاج ما يتصل بمشكلة البحث من أدلة وبراهين تبرهن على إجابة أسئلة البحث)) ومن ثم توظيف هذا المنهج في حصر ودراسة الآيات التي اشتملت على الشكر والوقوف على شروحها من خلال كتب التفاسير وأقوال العلماء.
The Holy Qur'an is: the constitution of life, not just a book to be read for the sake of reflection, and those who think about the verses that speak of thanksgiving realize that this great worship and this holy creation have been brought by Allah to be the way of life of the servants. One of the great worships that Allaah has bestowed on people is to thank him for the apparent and internal blessings, and to thank him as one of Allaah's rights to his servants. Almighty has commanded us in many places in his holy book The importance of the subject and the reasons for its choice: thanks to him have great places in religion, which is one of the ranks of which we worship and which we use; He ordered : him, and he was forbidden against him, and praised his family, and described him as the characteristics of his creation, and made him the end of his creation and command, and promised his family the best punishment, and made him a cause for more virtue, and a guard and a keeper of his grace, and told that his family is the beneficiaries With his verses. God has reminded him of his thanks, both of which are meant by creation and command, and patience is a servant for them and a means to them and help them, thanks are safe from the torment of God, because the shaker gets him safety from the torment of Allah Almighty other than the hypocrite exposed to the torment of Allah Almighty, god's century of thanks by faith, and that he has no purpose in the torment of creation if they say safe. Thanks is one of the most important reasons for god's satisfaction. Because of the importance of thanks and the greatness of his place in religion, The Lord used his mention in the research on this subject and his title (Thanks in the Holy Qur'an) with its branching and attaching the verses to each other in the words of thanks and the meanings of it, and divided the research into three chapters and mentioned the verses of thanks as required by the detective and related issues an objective explanatory study and its structure on the following plan: I have used the descriptive analytical method, which is known as (careful and accurate collection of records and available documents related to the subject of research, and then a comprehensive analysis of the contents of the research with a view to inferring the problem of research from evidence and evidence to prove the answer to the research questions)) and then employ this method in the inventory and study of the verses that included thanks and stand on their explanations through the books of interpretations and the words of scientists
Keywords: القرآن الكريم -- تفسير القرآن -- الشكر -- الدعوة الإسلامية